Controlling the supramolecular assembly of nucleosomes asymmetrically modified on H4. Issue 74 (1st September 2017) - Guidotti, Nora; Lechner, Carolin C.; Fierz, Beat
Abstract : We describe the iso lnc-tag, a traceless, protease-removable internal crosslinking tag, to control the assembly of nucleosomes asymmetrically modified on H4. Abstract : In stem cells, H4 proteins carrying different modifications coexist within single nucleosomes. For functional studies, we report the synthesis of such asymmetric nucleosomes. Asymmetry is achieved by transiently crosslinking H4 by a traceless, protease-removable tag introduced via an isopeptide linkage. These nucleosomes are used to study Set8 activity, a key methyltransferase.